1990
DOI: 10.1017/s0272263100009177
|View full text |Cite
|
Sign up to set email alerts
|

Attending to Form and Content in the Input

Abstract: This study explores the question of whether or not learners can consciously attend to both form and meaning when processing input. An experimental procedure is presented in which three levels of learners in four groups were asked to process information under four different conditions: attention to meaning alone; simultaneous attention to meaning and an important lexical item; simultaneous attention to meaning and a grammatical functor; and simultaneous attention to meaning and a verb form. Results suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
302
6
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 454 publications
(346 citation statements)
references
References 9 publications
30
302
6
8
Order By: Relevance
“…fluency, accuracy, and complexity) simultaneously, thus giving priority to one aspect of language at the expense of others. VanPatten (1990) agreed with the model and reported that learners often fail to direct their attention to fluency, accuracy, and complexity at the same time due to their limited attentional capacity. As a result, they have to channel their attention to one aspect of language at the price of others.…”
Section: Cognitive Task Complexitysupporting
confidence: 81%
“…fluency, accuracy, and complexity) simultaneously, thus giving priority to one aspect of language at the expense of others. VanPatten (1990) agreed with the model and reported that learners often fail to direct their attention to fluency, accuracy, and complexity at the same time due to their limited attentional capacity. As a result, they have to channel their attention to one aspect of language at the price of others.…”
Section: Cognitive Task Complexitysupporting
confidence: 81%
“…Contrary to Robinson's cognition hypothesis, Skehan (1998), through his limited capacity model, takes Van Patten's (1990) stance that learners would lose attention to form when they have to deal largely with content. Skehan (1998) argues that human beings have a limited capacity to process information.…”
Section: Theoretical Backgroundmentioning
confidence: 92%
“…Students at this level find a lot of interest being subjected to cognitive tasks about the systems of the language they are learning and are more likely to attend to form through meaning as demonstrated by Van Patten (1990). This will reduce the degree of distraction in the classroom and cultivate general interest in the course.…”
Section: Recommendationsmentioning
confidence: 99%